Interactive story telling package for children (Bahasa Malaysia version) / Hasnani Mohd Izazi - Hasnani , Mohd Izazi (1999)
Interactive Multimedia Storytelling Package is an interactive educational storytelling CD-ROM in Bahasa Malaysia meant for children aged 4 to 7 years old. It comprises of an interesting story suitable for preschools and can be beneficial teaching tool for parents and teachers in educating the young children. The story is written in simple Bahasa Malaysia to make it easier and comprehensible to local children. The story narrated aims to give them a lesson on humanity and morality with the characters playing a big role in influencing the children’s characteristics. To keep the children entertained as well as educated, this package also comprises games and activities to stimulate them intellectually. The activities incorporated are carefully selected in order to give the best experience to the children. The story includes activities such as coloring, counting and objects identifying which will help the children develop positive attitude and enhance their decision making and analytical skills. Director 7.0 is the software chosen to develop this programme.